PROBLEMS OF TEACHING TECHNICAL TERMINOLOGY IN THE NON-PHYLOLOGICAL UNIVERSITIES - Kushakov Y.X.; Bekimbetova Z.B.; Tulabayeve G. (Journal of new century innovations, 2022)
This article is about teaching technical terminology as an important part of the whole teaching activity. According to the authors a distinctive feature of scientific and technical texts is the abundance terms and various phrases, formulas, graphs, the translation of which can cause a number of difficulties. They point out that due to the rapid development technology in the scientific language, new terms (neologisms) constantly appear, which even the latest dictionary does not have time to fix, which also presents great difficulties in translation.